The Moderating Effect of Proactive Personality On Role Ambiguity And User Satisfaction: An Experimental Under Technostress Condition - Rohma, Frida Fanani; Zakiyah, Rahayu Dewi (Riset Akuntansi dan Keuangan Indonesia, 2021)
Abstract: The increasingly massive development of ICT (Information and Communication Technologies) makes the risk of technostress that triggers role ambiguity cannot be ignored. This study investigates the moderating effect of proactive personality on the relationship between role ambiguity and satisfaction. This study uses an experimental method involving 147 participants and placing participants in a state of technostress. Role ambiguity was categorized into 2 levels (high vs. low), proactive personality was categorized into 2 levels (confront vs. transform). The research findings show that the proactive personality (transform) has greater power in inducing user satisfaction than the proactive personality (confront). Proactive personality weakens the influence of role ambiguity on user satisfaction. Proactive personality as an individual innate factor can be elaborated as an attempt to filter the negative influence of role ambiguity on user satisfaction in ICT.